EFEKTIFITAS PEMBERIAN EKSTRA PUTIH TELUR TERHADAP PENINGKATAN KADAR ALBUMIN PADA PASIEN TUBERKULOSIS DENGAN HIPOALBUMIN - prastowo, agus; wiryatun, lestariana (Jurusan Kedokteran FK Unsoed, 2014)
Background. Tuberculosis is world health problem which is still need attention. Recently, tuberculosis in Indonesia as the third biggest after India and China. Albumin decrease significantly in tuberculosis patients, and causing it suspect is nutrition factors (low intake, anorexia, increasing catabolism), enteropati and acute protein reaction. Considering albumin function of the body is very important, food survey should be done for knowing what kind of food can increase albumin to tuberculosis patients. In this survey patients are given egg white extra.Objective. The purpose of this research wass to assess egg white intake associated with increasing albumin.Methods. A single blind randomized controlled trial was conducted at Margono Soekarjo Purwokerto hospital in 2013. Sampling technic is simple random sampling of 75 patientsÂ were allocated to study (n = 37) and a control (n = 38) goup. Both groups received high energy high protein diet, the study group received, additionally, an oral egg white-based on formula calculation Baxter for 14 days. Control group received, additionally, an extra soybean curd and mungbean powder. Albumin is checked before and after doing. Data is analyzed by Mann Whitney analysis to know different of albumin of two group.Results. Research results show average albumin before doing of study group is 2.82 g/dL and control group is 2.85 g/dL. Average albumin after doing of study group is 3.47 g/dL and control group is 2.81 g/dL. Bivariat analysis results show different significant of increasing albumin between study group and control group with p = 0.001 (p < 0.05).Conclusion. Egg white increase albumin to tuberculosis patients effectively.